Gender and age-group differences in hip muscle activity patterns in elite race walkers - Hanley, B.; Bissas, A.; Drake, A. (Slovak Journal of Sport Science, 2017)
Race walking is a complex activity that relies on considerable power generation by the muscles at the hip joint. Little is known, however, whether differences are present in terms of muscle activity patterns between men and women, or between younger and older athletes. The purpose of this study as to compare hip muscle activity patterns in elite male and female race walkers across U20 and senior age groups. Ten male and ten female race walkers participated, with five U20 and five senior athletes of each gender. The athletes were recorded using high-speed videography (100 Hz) as they race walked down a 40 m runway, during which the muscle activity of the gluteus medius, gluteus maximus, biceps femoris and rectus femoris was recorded using electromyography (EMG) (1000 Hz). The hip sagittal angle was calculated from digitised data, and average rectified EMG used to identify visual differences between groups. No differences were found using ANOVA between any groups for the activity of any of the four muscles analysed at toe-off, midswing, heel-strike and midstance, although there were visual differences in activity timings. Overall the few differences between groups showed that race walking techniques are comparable across trained athletes and coaches can adopt similar training practices when developing the muscular qualities of their athletes.